Dissecting the multi-omics landscape of TEAD1 in hepatocellular carcinoma: cycle regulation and metastatic potential - Huai, Ruiping; Mao, Canquan; Xiong, Lili (Frontiers in Immunology, 2025)
BackgroundThe effects exerted by the TEA domain transcription factor family genes on tumorigenesis in various cancers have been extensively investigated. Nevertheless, the potential role of TEAD1 in cancer-related epigenetic alterations, immunological characteristics, and prognosis remains ambiguous. This study aims to clarify the function and potential mechanisms of action of TEAD1 in cancer.MethodsWe assessed pan-cancer expression, methylation, and mutation profiles of TEAD1 to determine its prognostic significance in clinical settings. Furthermore, we analyzed the pan-cancer immunological landscape of TEAD1, with a particular focus on liver hepatocellular carcinoma (LIHC), using correlation analysis. We also performed a subtype-specific analysis of TEAD1 in LIHC to identify its expression patterns, immunological traits, and constructed a prognostic model based on disulfidptosis-related genes. Lastly, we assessed the impact of TEAD1 knockdown on LIHC cell lines HepG2 and Huh-7 by using in vitro experiments.ResultsOur findings suggest that TEAD1 is differentially expressed across various cancer types and can act as an independent prognostic factor for multiple cancers. Moreover, we observed that epigenetic changes involving TEAD1 are highly heterogeneous among several cancers; abnormal methylation and copy number variations were associated with a poor prognosis in multiple malignancies, especially in LIHC. Immunoassays demonstrated a significant association between TEAD1 and numerous immune checkpoints in LIHC. Additionally, cellular experiments revealed that knocking down TEAD1 reduced the proliferation, migration, and invasion capabilities of LIHC cells.ConclusionsThe results of this study imply that TEAD1 may serve as a promising prognostic biomarker for tumors and an immunotherapy target, while playing a crucial role in the proliferation, migration, and invasion processes within LIHC.